2017
DOI: 10.1089/lap.2016.0576
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impact of the Robotic Approach in Liver Surgery: A Comparative Study of Clinical Outcomes and Costs Between the Robotic and Open Technique in a Single Institution

Abstract: Background: One of the perceived major drawbacks of minimally invasive techniques has always been its cost. This is especially true for the robotic approach and is one of the main reasons that has prevented its wider acceptance among hospitals and surgeons. The aim of our study was to evaluate the clinical outcomes and economic impact of robotic and open liver surgery in a single institution.Methods: Sixty-eight robotic and 55 open hepatectomies were performed at our institution between January 1, 2009 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 44 publications
4
65
0
2
Order By: Relevance
“…Considering the high cost of purchasing and installing, and the yearly cost of maintenance (USD 2,200,000 and 150,000 respectively), it is evident that only high volume centers can employ this technology. However, when compared to open liver surgery, Daskalaki et al [33] demonstrated lower total cost, including readmissions, for robotic liver procedures (USD 41,948 vs. 37,518) along with significantly lower estimated blood loss, overall morbidity, and Clavien III/ IV complication rate. Nevertheless, according to Salloum et al [34], when considering the cost of purchasing a robotic platform installation (USD 2,200,000) and the annual cost of maintenance (USD 150,000 per year), robotic liver procedures appear to be much more expensive than conventional laparoscopic surgeries.…”
Section: Doi: 101159/000487686mentioning
confidence: 99%
“…Considering the high cost of purchasing and installing, and the yearly cost of maintenance (USD 2,200,000 and 150,000 respectively), it is evident that only high volume centers can employ this technology. However, when compared to open liver surgery, Daskalaki et al [33] demonstrated lower total cost, including readmissions, for robotic liver procedures (USD 41,948 vs. 37,518) along with significantly lower estimated blood loss, overall morbidity, and Clavien III/ IV complication rate. Nevertheless, according to Salloum et al [34], when considering the cost of purchasing a robotic platform installation (USD 2,200,000) and the annual cost of maintenance (USD 150,000 per year), robotic liver procedures appear to be much more expensive than conventional laparoscopic surgeries.…”
Section: Doi: 101159/000487686mentioning
confidence: 99%
“…Similarly, a study from the University of Illinois at Chicago demonstrated that postoperative outcomes after robotic liver procedures are related to lower rates of postoperative morbidity compared with the open approach group, including conversion to open (22% versus 40%; P = .047). Therefore, they concluded that robotic approach is not really a financial burden for hospitals . Conversely, Yu et al reported in their work comparing robotic and laparoscopic liver resections that the total medical cost was significantly higher in the robotic group (robot vs lap; $11.475 ± 2174 vs $6762 ± 1436, P = .001) .…”
Section: Discussionmentioning
confidence: 95%
“…While the operative time in live donor right hepatectomy is significantly longer compared with open procedures, there is no difference in complication rates, blood loss, and postoperative function of the liver remnant [2,45]. Decreased overall morbidity and intensive care unit and hospital stay are in favor of laparoscopic procedures while the operation per se adds tremendously to treatment cost, especially in the case of robotic systems being used.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased overall morbidity and intensive care unit and hospital stay are in favor of laparoscopic procedures while the operation per se adds tremendously to treatment cost, especially in the case of robotic systems being used. Taking into consideration the higher costs as well as the longer operating time, robotic-assisted donor right hepatectomy is not advantageous over conventional laparoscopic approaches [45].…”
Section: Resultsmentioning
confidence: 99%